1985
DOI: 10.1128/jb.161.2.602-608.1985
|View full text |Cite
|
Sign up to set email alerts
|

Repair of nonreplicating UV-irradiated DNA: cooperative dark repair by Escherichia coli uvr and phr functions

Abstract: The system previously used to study recombination of honreplicating UV-irradiated phage k DNA was adapted to study UV repair. Irradiated phages infected undamaged homoimmune lysogens. Pyrimidine dimer content (by treatment with Micrococcus luteus UV endonuclease and alkaline sucrose sedimentation) and a biological activity endpoint (infectivity in transfection of uvrB recA recB spheroplasts) were followed. Unless room light was excluded during DNA extraction procedures, photoreactivation (Phr function) was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Media and solutions TBY-broth, LB-broth-plates, and M9-minimal-plates have been described (26,27). TBY-Ap broth and LB-Ap plates contain 50 /g/ml ampicillin (Ap).…”
Section: Materials and Methods Bacteria And Bacteriophagesmentioning
confidence: 99%
“…Media and solutions TBY-broth, LB-broth-plates, and M9-minimal-plates have been described (26,27). TBY-Ap broth and LB-Ap plates contain 50 /g/ml ampicillin (Ap).…”
Section: Materials and Methods Bacteria And Bacteriophagesmentioning
confidence: 99%
“…The light-dependent repair of pyrimidine dimers has long been the sole known function of DNA photolyases. Only recently has evidence been obtained that in E. coli, photolyase also plays a role in the dark repair of dimers; both in vivo and in vitro studies indicate that this role is stimulation of nucleotide excision repair via interaction between photolyase and ABC excision nuclease (12,13,24,31,50,51). In this report, we have presented evidence that photolyase performs a similar function in yeast cells.…”
Section: Discussionmentioning
confidence: 71%
“…pathway (12,13,50,51). Several years ago, we demonstrated that this characteristic is due to photolyase-mediated enhancement of dimer recognition by ABC excision nuclease (31), which catalyzes the first step in nucleotide excision repair, namely, incision of the damage-containing strand on each side of the lesion (34).…”
mentioning
confidence: 99%
“…Plasmids: pCSR606 encodes the E. coli phr+ gene and some adjacent bacterial genes (SANCAR, SMITH and SANCAR 1983). pGG503 consists of a PstI fragment encoding the E. coli dam+ gene, inserted into pBR322 (HERMAN and MOD-Media and buffers: The following have been described elsewhere (HAYS, MARTIN and BHATIA 1985): TBM, TBMM, TBY and S broths; T A top agar; LBH and TCMB plates; T M , TMG and TS buffers; DNA buffer and extraction buffer. S-plates contain S-broth + 1% agar.…”
Section: Methodsmentioning
confidence: 99%